Thoracic Outlet Syndrome Part II: Consensus on the Management of Neurogenic Thoracic Outlet Syndrome by the European Association of Neurosurgical Societies' Section of Peripheral Nerve Surgery. Issue 2 (6th December 2022) - Rochkind, Shimon; Ferraresi, Stefano; Denisova, Natalia; Garozzo, Debora; Heinen, Christian; Alimehmeti, Ridvan; Capone, Crescenzo; Barone, Damiano G.; Zdunczyk, Anna; Pedro, Maria T.; Antoniadis, Gregor; Kaiser, Radek; et al.
Abstract : BACKGROUND: In the first part of this report, the European Association of Neurosurgical Societies' section of peripheral nerve surgery presented a systematic literature review and consensus statements on anatomy, classification, and diagnosis of thoracic outlet syndrome (TOS) along with a subclassification system of neurogenic TOS (nTOS). Because of the lack of level 1 evidence, especially regarding the management of nTOS, we now add a consensus statement on nTOS treatment among experienced neurosurgeons. OBJECTIVE: To document consensus and controversy on nTOS management, with emphasis on timing and types of surgical and nonsurgical nTOS treatment, and to support patient counseling and clinical decision-making within the neurosurgical community. METHODS: The literature available on PubMed/MEDLINE was systematically searched on February 13, 2021, and yielded 2853 results. Screening and classification of abstracts was performed. In an online meeting that was held on December 16, 2021, 14 recommendations on nTOS management were developed and refined in a group process according to the Delphi consensus method. RESULTS: Five RCTs reported on management strategies in nTOS. Three prospective observational studies present outcomes after therapeutic interventions. Fourteen statements on nonsurgical nTOS treatment, timing, and type of surgical therapy were developed. Within our expert group, the agreement rate was high with a mean of 97.8% (± 0.04) for each statement, ranging between 86.7% and 100%. CONCLUSION: Our work may help to improve clinical decision-making among the neurosurgical community and may guide nonspecialized or inexperienced neurosurgeons with initial patient management before patient referral to a specialized center. Abstract :